Statistical power analysis a simple and general model for traditional and modern hypothesis tests - Murphy, Kevin; Myors, Brett (Routledge, 2023)
"Statistical Power Analysis explains the key concepts in statistical power analysis and illustrates their application in both tests of traditional null hypotheses (that treatments or interventions have no effect in the population) and in tests of the minimum-effect hypotheses (that the population effects of treatments or interventions are so small that they can be safely treated as unimportant). It provides readers with the tools to understand and perform power analyses for virtually all the statistical methods used in the social and behavioral sciences. Brett Myors and Kevin Murphy apply the latest approaches of power analysis to both null hypothesis and minimum-effect testing using the same basic unified model. The book starts with a review of the key concepts that underly statistical power. It goes on to show how to perform and interpret power analyses, and the ways to use them to diagnose and plan research. We discuss the uses of power analysis in correlation and regression, in the analysis of experimental data, and in multilevel studies. This edition includes new material and new power software. The programs used for power analysis in this book have been re-written in R, a language that is widely used and freely available. The authors include R codes for all programs, and we have also provided a web-based app that allows users who are not comfortable with R to perform a wide range of analyses using any computer or device that provides access to the web. Statistical Power Analysis helps readers design studies, diagnose existing studies, and understand why hypothesis tests come out the way they do. The fifth edition includes updates to all chapters to accommodate the most current scholarship, as well as recalculations of all examples. The book is intended for graduate students and faculty in the behavioral and social sciences, researchers in other fields will find the concepts and methods laid out here valuable and applicable to studies in many domains"--
Revised edition of Statistical power analysis, 2014. - Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on August 28, 2023)
Keywords: Statistical hypothesis testing; Statistical power analysis; Tests d'hypothèses (Statistique); Analyse de puissance (Statistique); PSYCHOLOGY / Statistics; PSYCHOLOGY / Research & Methodology